Family climate and coping with stress in cancer patients - Díaz A., Gloria (2010)
Cancer is a disease that increasing twice in the last thirty years. The present investigation aims to establish the relationship between family environment and coping with stress in cancer patients Edgardo Rebagliati Martins Hospital (HERM). Bearing in mind of the impact that disease oncology has serious effects not only the patient but also in the family system. Descriptive method was used to correlate with the aim of describing and relating the ways of coping and dimensions of family environment in patients with cancer in the first phase. The sample consisted of 287 subjects being most married people, technical and higher education, female and male and averaged of 54 years. Were used as tools Social Climate Scale Family - Moos FES (1982) and the Questionnaire of Coping to stress in cancer patients – CAEPO González (2004). The results indicate that the development dimension is affected to a greater extent due to the decline in social activities of the family for most of this dedication to patient care. A significant relationship was found, between family environmental suitable and positive coping, just as relations between the dimension relationship and Coping and Active Control, Self-control and emotional control. By taking into account gender differences is that women tend to use active cognitive strategies of positive reinterpretation greater extent than men, besides patients with Breast Cancer, use positive coping strategies to stress in relation to other types, and conversely those suffering from thyroid cancer, lymphoma No Hodking and prostate cancer not show feelings of uncertainty regarding the development and future of their disease.